APLIKASI PEMETAAN LOKASI KOS DI KAWASAN POLMAN NEGERI BABEL BERBASIS WEBSITE - Mutrinitami Tamzil; Yang Agita Rindri; Irwan Irwan (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
The number of students or workers who come to the Polman Negeri Babel area causes the need for boarding houses to increase, however, the availability of information about the location of boarding houses is very limited, making it difficult to find the location of the boarding house that is desired. Therefore, a website-based boarding location mapping application was made which aims to implement a geographic information system using Maps Leaflets which can make it easier for users to find information about boarding houses in the Polman Negeri Babel area and can assist boarding house owners in spreading their boarding houses. This system is made using the waterfall method in order to produce a systematic and sequential system design. In making the system design using use case diagrams and system testing using the blackbox method. The results of making this website-based boarding location mapping application can provide information to users to make it easier to find boarding locations and other information such as facilities, prices, addresses, and the owner's cellphone number.